Logo Counseling for Low Spiritual Self-Esteem Among College Students - Jacob Daan Engel; Lobby Loekmono (International Journal of Evaluation and Research in Education (IJERE), 2018)
The purpose of this research was to examine logo counseling model in improving low spiritual self-esteem problem for college students. This research used descriptive method and quasi-experiment method with a non-equivalent pre-test-post-test control group design. The results then analyzed from the statistical significance and the practical significance. The result showed that logo counseling model could improve low spiritual self-esteem among college students, indicated by statistical significance of tcount (43.851) > ttable (2.144) and N-gain of the experimental group (0.75) > N-gain of the control group (0.15) and practical significance of positive attitude, behavior and value changes. Recommendation also given for related agencies to implement logo counseling model in training program and for further research by related experts in the field.